EDITORNAL OFFICES OF KYRGYZ RADIO AND THE ACTIVITIES OF JOURNALISTS IN 1970-85 (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The article narrates history of Kyrgyz radio, broadcast for more than 80 years, the radio edition of 1970-85. The staff workers and their contribution to the development of Kyrgyz radio. The technical equipment, the main direction of the programs of the period so-called «social calm» .
Keywords: senek, kyrgyz padio, journalist, propaganda, soviet, genre, program, editorial, ether.